Effect of carbon nanotubes on the flexural properties and flammability of carbon fibre/epoxy multi‐scale composites. Issue 12 (14th December 2022) - Zulkifli, N.A.; Ismail, N.H.; Jaafar, M.; Othman, A.R.
Abstract: The aim of the present study is to investigate the coating effect of different amount of multi‐walled carbon nanotube on woven carbon fibre fabric. In the study, multi‐scale composites were produced using hybrid reinforcement consist of woven carbon fibre coated with multi‐walled carbon nanotubes. The coated fibres were stacked together with epoxy binder to produce composite laminates by using hand lay‐up method, followed by vacuum bagging. Measurements using zeta potential and ultraviolet‐visible analysis indicate that multi‐walled carbon nanotubes have good dispersion in water with the help of gum arabic. Multi‐walled carbon nanotubes suspension was spray coated on carbon fibre fabric at different concentrations (0.3 wt.%, 0.5 wt.%, 0.8 wt.% and 1.0 wt.%). The flexural strength and flexural modulus increased by 24 % and 34 % with addition of multi‐walled carbon nanotubes, respectively. Based on the flexural properties, 2‐ply carbon fibre /epoxy composites with 0.5 wt.% multi‐walled carbon nanotubes multiscale composite showed higher flexural strength and comparable flexural modulus compared with other composites laminates. Furthermore, the presence of multi‐walled carbon nanotubes in the carbon fibre composites reduced flammability of the composites by decreasing the burning rate of the composites containing high concentration of multi‐walled carbon nanotubes. Abstract : In this study, multi‐scale carbon fibre reinforced epoxy composites were prepared by incorporating multi‐walled carbon nanotubes onto carbon fibres through spray coating process. The composites provide enhanced flexural properties and reduced flammability.